2021
DOI: 10.1021/jacs.1c00290
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Dynamic Metalation State of New Delhi Metallo-β-lactamase-1 in Bacteria Using a Reversible Fluorescent Probe

Abstract: New Delhi Metallo-β-lactamase (NDM) grants resistance to a broad spectrum of β-lactam antibiotics including last-resort carbapenems and is emerging as a global antibiotic resistance threat. Limited zinc availability adversely impacts the ability of NDM-1 to provide resistance, but a number of clinical variants have emerged that are more resistant to zinc scarcity (e.g., NDM-15). To provide a novel tool to better study metal ion sequestration in host-pathogen interactions, we describe the development of a fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The horizontal transfer of plasmid-mediated resistance determinants has become a severe threat to the clinical efficacy of antibiotics, in hospital and community settings, triggering the onset of a worldwide antimicrobial resistance crisis. ,, Among them, subclass B1 MβLs including the clinically important NDM-, IMP-, and VIM-type variants and class A KPC-type and class D OXA-type serine carbapenemases are mostly encoded on plasmids in clinical isolates of Acinetobacter spp ., Pseudomonas spp., and Enterobacteriaceae , giving rise to the emergence and spread of MDR Gram-negative pathogens, which threaten the ability to effectively treat hospital-acquired infections. Global antibiotic resistance has reached critical levels, with major bacterial pathogens, including Gram-negative organisms such as A. baumannii , P. aeruginosa , E. coli , and K. pneumoniae , quickly evolving toward pan-drug-resistant phenotypes. , There is an urgent medical need for strategies that address this carbapenem resistance. , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The horizontal transfer of plasmid-mediated resistance determinants has become a severe threat to the clinical efficacy of antibiotics, in hospital and community settings, triggering the onset of a worldwide antimicrobial resistance crisis. ,, Among them, subclass B1 MβLs including the clinically important NDM-, IMP-, and VIM-type variants and class A KPC-type and class D OXA-type serine carbapenemases are mostly encoded on plasmids in clinical isolates of Acinetobacter spp ., Pseudomonas spp., and Enterobacteriaceae , giving rise to the emergence and spread of MDR Gram-negative pathogens, which threaten the ability to effectively treat hospital-acquired infections. Global antibiotic resistance has reached critical levels, with major bacterial pathogens, including Gram-negative organisms such as A. baumannii , P. aeruginosa , E. coli , and K. pneumoniae , quickly evolving toward pan-drug-resistant phenotypes. , There is an urgent medical need for strategies that address this carbapenem resistance. , …”
Section: Introductionmentioning
confidence: 99%
“…32−34 Global antibiotic resistance has reached critical levels, with major bacterial pathogens, including Gram-negative organisms such as A. baumannii, P. aeruginosa, E. coli, and K. pneumoniae, quickly evolving toward pan-drug-resistant phenotypes. 35,36 There is an urgent medical need for strategies that address this carbapenem resistance. 37,38 β-Lactam antibiotics in combination with β-lactamase inhibitors have been demonstrated as a clinically effective strategy to overcome β-lactamase-mediated resistance.…”
Section: Introductionmentioning
confidence: 99%
“…17,69 An enhanced luminescence of Pd−ZPP(Fe) (10.0 μM) appeared at both 648 and 714 nm upon the addition of FDH (total 0.5 μM) (Figure 4c). 70 Notably, this spectra revealed significant changes from an initial linear growth to almost unchanged (Figure S27), which could be interpreted as the steady binding between Pd−ZPP(Fe) and enzyme FDH arising from recognition between them. 18,71 Importantly, circular dichroism and luminescence spectra showed that the characteristic peaks attributable to FDH were basically maintained after adding the capsule Pd−ZPP(Fe) and prolonging time, suggesting the stability of the combined system with the secondary and tertiary structures of FDH preserved (Figures S30−S32).…”
Section: Tandem Catalysis By Artificial and Natural Enzymesmentioning
confidence: 94%
“…The conformation of the probe was changed by AmpC, which led to the phenomenon of AIE [ 102 ]. Mehta et al conjugated an environmentally sensitive fluorophore onto a mercaptan-based scaffold of New Delhi metallo- β -lactamase (NDM) inhibitors (probe 35 ) to monitor the dynamic metalation of NDM in E. coli and for fluorescence imaging [ 103 ].…”
Section: Identification Of Endogenous Enzymes Of Pathogenic Bacteriamentioning
confidence: 99%